2013
DOI: 10.1016/j.bbmt.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Analyses Demonstrate Significant Clinical Effects of Minor Histocompatibility Antigens on GvHD and GvL after HLA-Matched Related and Unrelated Hematopoietic Stem Cell Transplantation

Abstract: The effect of minor H antigen mismatching on the occurrence of graft-versus-host disease (GvHD) and graft-versus-leukemia (GvL) after HLA-matched hematopoietic stem cell transplantation (HSCT) has mainly been demonstrated in single-center studies. Yet, the International Histocompatibility and Immunogenetics Workshops (IHIW) provide a collaborative platform to execute crucial large studies. In collaboration with 20 laboratories of the IHIW, the roles of 10 autosomal and 10 Y chromosome-encoded minor H antigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 34 publications
5
58
0
4
Order By: Relevance
“…In both HLA-matched and HLA-mismatched settings, T-cell recognition of minor histocompatibility antigens contributes to both GVHD and GVL. 29 Thus, employing an APC sharing lineage with a patient's-specific tumor may unfavorably deplete donor T cells recognizing minor antigens identifying the tumor, reducing the GVL response. Selective depletion has been achieved with a variety of stimulator types such as unmanipulated PBMCs, 30 ex vivo expanded CD8 + T lymphocytes, 31 and EBV-transformed B lymphoblastoid cell lines (EBV-LCL).…”
Section: Discussionmentioning
confidence: 99%
“…In both HLA-matched and HLA-mismatched settings, T-cell recognition of minor histocompatibility antigens contributes to both GVHD and GVL. 29 Thus, employing an APC sharing lineage with a patient's-specific tumor may unfavorably deplete donor T cells recognizing minor antigens identifying the tumor, reducing the GVL response. Selective depletion has been achieved with a variety of stimulator types such as unmanipulated PBMCs, 30 ex vivo expanded CD8 + T lymphocytes, 31 and EBV-transformed B lymphoblastoid cell lines (EBV-LCL).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of smaller cohorts of patient-donor pairs by other groups have detected a similar association. 14,15 More recently, Spierings et al 16 carried out a multicenter analysis exploring the clinical impact of several mHags on GVHD in a cohort of 639 patients receiving an allogeneic HSCT from an HLA-identical related donor and 210 from an unrelated donor. Although they tried to explore the role of mismatches for the mHags UGT2B17/A29 and UGT2B17/B44, the analysis could not be addressed because of the low numbers of relevant mismatched pairs, and they did not assess the impact on clinical outcome of the UGT2B17 mismatch regardless of the MHC restriction.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, for HY mismatches a reduced risk of relapse was clearly suggested, 42,43 whereas for hematopoietic-specific mHags such as HA-1 an association between GvT and mHag mismatch was also demonstrated in a relatively large cohort of 285 HLA-A2-positive CML patients, but exclusively when GvHD was also present. 44,45 Several follow-up studies were unable to demonstrate the association of specific mHag mismatches with either GvHD or GvT, possibly due to the small cohort size, 46-48 but a recent study investigating a large number of patients did demonstrate improved disease-free survival when at least one mHag mismatch was present, particularly in multiple myeloma patients. 49 Moreover, in a large retrospective study, allo-SCT from female donors to male recipients was found to have significantly lower relapse rates in comparison with all other gender combinations, indicating an important GvT effect mediated by HY responses.…”
Section: Identification Of Mhags By Reverse Immunology Strategymentioning
confidence: 99%